Przedmowa w pierwszych (napisanych po polsku) traktatach matematycznych = The prefaces written to Polish earliest mathematical treatises - Biniewicz, Jerzy (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article brings some reflections upon prefaces written to Polish earliest mathematical treatises (16th and 17th centuries), which can be regarded as textbooks. The preface as a statement which cross-refers readers to a text by the same author is a text-making instrument, since it draws a map of the base text, and presents the structure of the argument.
Keywords: dyskurs naukowy; gatunek mowy; gatunek metatekstowy; podręcznik; przedmowa; scientific discourse; genre of speech; metatext; textbook; preface